Risk stratification in laminopathies and Emery Dreifuss muscular dystrophy - Abdallah Fayssoil (MDPI AG, 2018)
Laminopathies are genetic disorders due to gene mutation encoding for proteins of the nuclear envelope. Patients are at risk of conduction defect, arrhythmia, sudden death and heart failure. The authors summarize predictive factors for cardiac events reported in the literature in this group of disease.